Saving in Southeast Asia and Latin America Compared : Searching for Policy Lessons - Thimann, Christian (IMF Working Papers; Working Paper, 1997)
This paper examines empirical determinants of private saving for a sample of economies in Southeast Asia and Latin America over the period 1975-95. It uses panel estimations to establish relationships between private saving rates and a range of policy and nonpolicy variables. The findings show that fiscal policy, particularly social security arrangements, influence private saving; also macroeconomic stability and financial deepening appear to have been important in accounting for differences in saving behavior between the two regions.